ANALYZING INTERNET USAGE AND ONLINE SHOPPING FOR INTERNATIONAL CONSUMERS - VINEREAN, Simona; CETINĂ, Iuliana; DUMITRESCU, Luigi (Annales Universitatis Apulensis Series Oeconomica, 2014)
Currently, the buying decision process model is undergoing changes due to new and multiple points of interaction to which consumers are exposed. In this new business framework, there are very few business strategies that do not consider the online component, and via the Internet, interactive marketing offers unique benefits. As consumers get more and more acquainted with the Internet, in general, they are also becoming more prone to Internet retailing. In this development of the online buying process, companies can adapt their messages to engage consumers by reflecting their special interests and past recorded behavior. Thus, in this paper, we explore how online retailers can gain new perspectives on their customers’ online shopping predisposition based on their experience with the Internet and frequency of use